Flesh and blood - Cornwell, Patricia Daniels (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2014)
Scarpetta finds herself in the unsettling pursuit of a serial sniper who leaves no incriminating evidence except fragments of copper. Then she comes face to face with shocking evidence that implicates her techno-genius niece, Lucy, Scarpetta's own flesh and blood.
Keywords: Scarpetta, Kay (Fictitious character) -- Fiction; Forensic pathologists -- Fiction; Women pathologists -- Fiction; Snipers -- Fiction; Serial murder investigation -- Fiction; Mystery fiction; Suspense fiction